Urban Transformation as a tool for Disaster Mitigation - Handan Turkoglu; Seda Kundak (European Regional Science Association (ERSA), 2011)
Urban transformation projects are prepared with the purpose to sanitize decayed areas, to make cities beautiful and to create economic vitality. Since natural hazards threaten large metropolitan areas, urban transformation is pronounced together to mitigate disasters. This approach of urban transformation includes land use decisions related to hazard, risk and vulnerability analysis and to enhance the implementation of building codes respecting the current standards with application of urban transformation methodologies. Ideally urban transformation methodologies include not only physical and economic improvement but also provide social improvement concerning people who live in the area. Urban transformation seems to be the government's primary tool for disaster mitigation by guiding urban development and improving the quality of housing stock in Turkey. Several attempts since 2005 to pass a bill to institutionalize this controversial strategy finally succeeded in 2010. In June, Law No. 5998, an amendment to Municipal Law No5393 of 2005, expanded item 73 on urban transformation projects to give municipalities the power to initiate Urban Transformation projects to rehabilitate urban areas or to mitigate disaster risk. According to this item in metropolitan areas, district municipalities can implement such projects within their jurisdictions with the approval of the metropolitan municipal council. Therefore Istanbul (Turkey) which is the biggest metropolitan area and waiting a big earthquake in next 30 years will be subjected to several urban transformation projects in the near future. In the paper, the urban transformation related to disaster mitigation approach will be discussed in the case of Istanbul in terms of descriptive analysis and proposals for future development.
Keywords: 330